2022
DOI: 10.26434/chemrxiv-2022-8hnrh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BacPROTAC-induced degradation of ClpC1 as a new strategy against drug-resistant mycobacteria

Abstract: Antimicrobial resistance (AMR) is a global public health threat that urgently requires development of new treatment concepts. In general, these treatments should not only be able to overcome existing resistance, but designed to slow down or prevent emergence of new resistance mechanisms. Targeted protein degradation (TPD), whereby a drug redirects cellular proteolytic machinery towards degrading a specific target, is an emerging concept in drug discovery. Here, we demonstrate that a TPD strategy represents an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…A simplified desoxycyclomarin derivative was used as the active compound for the development of BacPROTAC against the tuberculosis H37Rv strains residing on the THP-1 macrophages. Homo-BacPROTAC molecule was made by dimerizing the cyclomarin molecules, and it was known to show high degradation efficiency at the sub-nM level [ 65 ].…”
Section: Prokaryotic Systemmentioning
confidence: 99%
“…A simplified desoxycyclomarin derivative was used as the active compound for the development of BacPROTAC against the tuberculosis H37Rv strains residing on the THP-1 macrophages. Homo-BacPROTAC molecule was made by dimerizing the cyclomarin molecules, and it was known to show high degradation efficiency at the sub-nM level [ 65 ].…”
Section: Prokaryotic Systemmentioning
confidence: 99%
“…Phenotypic assays against Mycobacterium tuberculosis showed that CymA was active against several MDR-TB clinical isolates and hypoxic non replicating bacillus, without effects against Gram-negative and Gram-positive bacteria (Schimitt et al, 2011b). Using molecular modification approach, it was synthesized a cyclic peptide with a slightly simplified structure, named desoxycyclomarin C (dCym) (Junk et al, 2023). Chemical structure of BacPROTACs-1, -2 and -3.…”
mentioning
confidence: 99%